Some characteristics and propagation of whistler-mode LF/MF emissions as observed at low altitudes above the Antarctic region with ISIS-1 - Aikyo, Kazuhiro; Ondoh, Tadanori; Ohtaka, Kazuhiro (National Institute of Polar Research, 1988)
P(論文) The broadband whistler-mode (w-mode) emissions in LF/MF bands observed at low altitudes in the nighttime auroral zone are examined in detail, especially from the viewpoint of the spectral characteristics and directions of wave vectors of the emissions using the ISIS-1 data including the fixed and swept frequency ionograms and AGC voltage traces of the sounder receiver. The emissions are characterized by spectra with relatively sharp upper cutoff ranging 0.75 to 0.4f_H (f_H : electron gyrofrequency) and with lower frequency cutoff less than 0.1 MHz (the lowest frequency of the sounder) for many cases. The directions of wave vectors at the satellite are determined from the antenna orientation at the instant when the emissions exhibit intensity minima on AGC voltage traces in the fixed frequency mode. The resultant directions of wave vectors are used as initial conditions for ray tracing to locate the source regions and to know the directions of wave vectors at the source region. It is shown that the cyclotron maser instability driven by auroral electron with upward loss cone at low altitudes is the most probable source mechanism which explains some characteristics of the observed emissions, particularly, of their high frequency portion. departmental bulletin paper